School Literacy Movement Through Reading Corner at SLB B Yakut Purwokerto - Sholikhati, Nur Indah; Cakrawati, Laxmi Mustika; Yulianti, Uki Hares (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
TThe government initiated the School Literacy Movement (in Indonesian: Gerakan Literasi Sekolah or GLS) program in the Merdeka Curriculum as an effort to foster a culture of student literacy. This program requires schools to have a special program to optimize the School Literacy Movement. Meanwhile, there are obstacles in implementing the literacy movement in schools, namely the lack of literacy training for students with special needs in schools and the lack of availability of books at SLB B Yakut. With this reading corner literacy program based on local wisdom, it is hoped that this can be a solution to the problems above. The importance of literacy culture is to develop basic abilities and skills for a person in acquiring knowledge, skills, as well as forming attitudes for deaf-speech students so that they care about local wisdom culture. The purpose of carrying out this service is 1) to describe the implementation of GLS through reading corners and 2) to explain the impact of using local wisdom-based reading corners in SLB B Yakut. Methods for implementing service include: (1) approach methods taken starting from surveys, licensing, and providing motivation to teachers who will take part in training (2) program implementation methods, including the preliminary stage, socialization and audience stages, implementation stage, and monitoring stage and evaluation. As a result of this activity, students with special needs are expected to have literacy habits through reading corners at school. The strategy in the school literacy movement through reading corners prioritizes the affective social environment as a model of literate communication and conditions the physical environment to be literacy-friendly, such as making teachers role models in implementing the school literacy movement.